2-Amino-3-methyl-3-(4-nitrophenyl)-5-(phenylthio)-3H-pyrrole-4-carbonitrile as effective corrosion inhibitor for mild steel in 1M HCl: Thermodynamical, electrochemical, surface and theoretical calculat ion - Verma C.; Quraishi M.A. (My University, 2025)
Present work describes the corrosion inhibition efficiency of 2-amino-3-methyl-3-(4-nitrophenyl)-5-(phenylthio)-3H-pyrrole-4-carbonitrile (INH) on mild steel in 1M HCl using weight loss, electrochemical, surface and molecular dynamics simulation methods. The weight loss results show that inhibition efficiency increasing with increasing INH concentration and maximum value was obtained at 50 mg/L concentration. Adsorption of the INH on mild steel surface obeys the Langmuir adsorption isotherm. Potentiodynamic polarization study suggests that investigated INH acts as mixed type inhibitor. EIS study indicates that the INH forms a protective surface film at metal/electrolyte interface. Both SEM and AFM studies show that surface smoothness increases due to formation of protective surface film by INH. The Monte Carlo simulation study suggests that INH has strong tendency to adsorb on mild steel surface in 1M HCl. The weight loss, electrochemical, surface and molecular dynamics calculations are in good agreement. © 2016 Faculty of Engineering, Ain Shams University. Production and hosting by Elsevier B.V.